2008
DOI: 10.1038/ejhg.2008.203
|View full text |Cite
|
Sign up to set email alerts
|

Promoter polymorphism of matrilin-1 gene predisposes to adolescent idiopathic scoliosis in a Chinese population

Abstract: Adolescent idiopathic scoliosis (AIS) is widely recognized as a complex disorder with a strong genetic predisposition. In previous studies, a number of extracellular matrixes (ECMs) related genes have been duplicated as candidate genes for AIS. Matrilin-1 plays an important role in the organization of the ECM, and matrilin-1 gene (MATN1) mutant mice showed similar phenotypes to scoliosis. We hypothesized that MATN1 was a candidate predisposition gene for AIS. A gene-based association study was conducted using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
61
1
3

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 90 publications
(65 citation statements)
references
References 41 publications
(24 reference statements)
0
61
1
3
Order By: Relevance
“…The previously reported association of rs1149048, rs10488682, and rs4753426 with AIS predisposition found in Chinese [19][20][21] was not replicated in our study (Table 1). This lack of replication is not unusual in genetic-association studies of common diseases.…”
Section: Discussioncontrasting
confidence: 54%
See 4 more Smart Citations
“…The previously reported association of rs1149048, rs10488682, and rs4753426 with AIS predisposition found in Chinese [19][20][21] was not replicated in our study (Table 1). This lack of replication is not unusual in genetic-association studies of common diseases.…”
Section: Discussioncontrasting
confidence: 54%
“…Chen et al 19 reported an association between rs1149048 and curve severity in a study of 267 AIS cases, and Yeung et al 22 reported an association between rs5742612 and curve severity in a study of 340 AIS cases. However, these associations were not replicated in our analysis of 538 cases (Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations